Analisis Implementasi Kebijakan Insentif Pajak Di Masa Pandemi Covid – 19 Atas Pajak Penghasilan Pasal 21 Pegawai Negeri Sipil Di Uptd Puskesmas Telaga Murni Kabupaten Bekasi Tahun 2020 - Nurmalasari Nurmalasari; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to analyze the implementation of article 21 income tax incentives at the Department of technical implementing elements of the Telaga Murni Health Center. The phenomenon of this research is regarding tax incentive policies issued by the government, especially on article 21 income tax for civil servants. As well as what obstacles are experienced in the application of the article 21 income tax incentive policy. In this study, the authors used qualitative research methods with qualitative descriptive analysis. The data collection was carried out in natural conditions, primary data sources, and data collection techniques were more on participatory observation and interviews. Determination of informants using purposive sampling technique, namely Informants who are considered to have knowledge or information about a particular thing or event. which was the informants who were deemed to have knowledge or information about a particular thing or event. In this study, the informants were Civil Servants who worked at the Telaga Murni Health Center for the 2020 period. The results of the study concluded that the implementation of Article 21 Income Tax Incentive policy at the Telaga Murni Health Center was good enough because in terms of quantity and quality so that it could run and achieve its goals. in the use of Article 21 income tax incentives.